Enhancing access to research in institutional repositories through API - Miller, Ryan; Yerramareddy, Indira (2014)
IFPRI (International Food Policy Research Institute) recently completed a project where we shared IFPRI research papers with a partner organization, the Land Portal (a collaboration of The International Land Coalition (ILC) and Landtenure.info) from our open access repository. The project began when the IFPRI Knowledge Management team was approached by the Land Portal with a request for help finding a way to share a feed for papers from IFPRI related to land and land issues on their website. In this paper, we document our experience using API calls to IFPRI's institutional repository to feed publication metadata records to our partner's website. We used this technique to promote and share the intellectual output of IFPRI with the LandPortal.info and ReSAKSS-Asia project. As a result of this project, we have achieved increased access to IFPRI research, improved reach for our researchers, and enhanced value of the content on our partner's website.